The relationship between self-efficacy and the duration of students’ final project writing completion - Nafisa Syahida Rahmadini; Hartono Hartono; Rohmaniyah Rohmaniyah (Universitas Islam Sultan Agung, 2019)
This study is aimed at finding out the relationship between self-efficacy and the duration of students' final project writing–commonly reffered as skripsi-completion. It was a correlational study involving 33 students of English Education and English Literature departments of the College of Languages and Communication Science of Sultan Agung Islamic University (UNISSULA) Semarang who were taken purposively as samples for the study. Data were collected by questionnaire of self-efficacy and a respondent-fill-form to collect data on the duration the final project completion. The result of the analysis showed that students’ self-efficacy and the duration of their final project writing completion was correlated positively at 0.994. This implies that students with high self-efficacy would likely complete the final project earlier than those with lower self-efficacy.